DETERMINATION OF THE PRESENCE OF NANO-PLASTIC IN BOTTLED DRINKING WATER IN THE REPUBLIC OF MACEDONIA BY APPLYING THE SEM-EDS METHOD (Natural Resources and Technology, 2019)
The material presents the preliminary results of the testing for the presence of micro plastic (nano-particles) in the bottled drinking water in Macedonia by applying the method CEM-EDS.The term plastic refers to any synthetic or semi-synthetic polymer with thermo-plastic or thermal characteristics, which can be synthesized from hydrocarbons or biomass. The production of plastic mass exponentially increases with the increase in its application, from 1 million tons in 1945 to over 300 million tons in 2014. Some of the characteristics of plastic arising from the very process of its production can pose a problem in the environment. Its low weight contributes to its spread over very large distances, while at the same time it is resistant to the processes of surface degradation. These characteristics are a consequence of its chemical structure. In many cases, this incoherent hydrocarbon chain structure may be food for a particular type of microorganisms. The plastic is also fragmented into small particles by means of photo-oxidative mechanisms). These small micro particles or nano-particles of plastic can be found in many parts of the environment (water, soil, food) and they very easily pass through the gastrointestinal tract.